Alcohol Drinking and the Risk of Chronic Kidney Damage: A Meta‐Analysis of 15 Prospective Cohort Studies. (5th June 2019) - Li, Deming; Xu, Jiuhong; Liu, Fang; Wang, Xinjing; Yang, Huanhuan; Li, Xinli
Abstract : The relationship between alcohol drinking and chronic kidney damage, mainly including declined glomerular filtration rate (GFR), proteinuria, and end‐stage renal disease, was conflicting. Thus, a meta‐analysis was conducted to investigate their potential associations. PubMed and Web of Science were searched to identify prospective studies assessing the associations between alcohol drinking and chronic kidney damage published up to March 2019. Random‐effects model was employed to pool the relative risks (RR) with 95% confidence intervals (CIs). Subgroup meta‐analyses stratified by the basic characteristics of subjects were performed. A total of 15 cohort studies were included in the present study, with 268, 723 participants and 31, 766 incident cases. Participants with low (<13 g/d), moderate (13 to 26 g/d), and high (26 to 60 g/d) dose of alcohol drinking had 12% (RR: 0.88, 95% CI: 0.83 to 0.93), 24% (RR: 0.76, 95% CI: 0.70 to 0.83), and 21% (RR: 0.79, 95% CI: 0.71 to 0.88) lower risk of chronic kidney damage compared with the reference group (non‐ or occasional drinkers), respectively. The lower risk for chronic kidney damage remained significant for the declined GFR, or in men, or for participants aged less than 55 yrs, or studies with longer than 8 yrs of follow‐up, while severe alcohol drinking (≥60 g/d) insignificantly increased 7% risk of chronic kidney damage (RR: 1.07, 95% CI: 0.53 to 2.15). No obvious heterogeneity and no publication bias were observed. Based on our meta‐analysis, participants with alcohol drinking less than 60 g/d were at lower risk of declined GFR, especially in men or participants aged less than 55 yrs. Much more prospective cohort studies are required to confirm our present findings. Abstract : The forest plot of low alcohol drinking (<12 g/d) and the risk of chronic kidney damage. The subjects with low alcohol drinking had 11% lower risk of kidney damage compared with the reference group (RR = 0.89, 95% CI: 0.84–0.95).